The relationship between determinants of husband–wife agreement and household climate change mitigation behavior - Hung, Li-San; Li, Yen-Wei; Bayrak, Mucahid Mustafa (Environmental Research Communications, 2023)
Reducing carbon emissions from household activities is an important element in achieving climate goals. Engagement in household climate change mitigation behaviors usually requires interaction and negotiation among household members. Congruence theory suggests that individual-determinants of climate change mitigation behavior are strongly influenced by household-level determinants, such as mutual agreement between couples, but few studies have empirically tested this hypothesis. Being a pioneer study of its kind in the field of climate change mitigation behavior, a unique dataset that contained the survey results of 152 married heterosexual couples in Taipei City, Taiwan was used to test the congruence effect on household climate change mitigation behaviors. Eight theoretical determinants of household climate change mitigation behaviors (five at individual-level and three at household-level) and the level of engagement in three household climate change mitigation behaviors were analyzed. Results from a response surface analysis suggested that none of the five individual-level determinants exhibited congruence effects, while two out of three household-level determinants exerted congruence effects on the behavior of energy-efficient appliance purchasing. In other words, based on the results of this study, married heterosexual couples having similar attitudes regarding household-level variables but not individual-level variables is a nonnegligible factor influencing engagement in household climate change mitigation behaviors that require a certain level of intrahousehold interactions.